ANALISIS PERTIMBANGAN HUKUM HAKIM DALAM PUTUSAN NIET ONTVANKELIJKE VERKLAARD (N.O) NOMOR 18/Pdt.G/2020/Pa.Lbh - NIM. A1011211293, FIERELDA ADINDA (Fakultas Hukum Universitas Tanjungpura, 2025)
AbstractIn Case Number 18/Pdt.G/2020/Pa.Lbh, the panel of judges of the Labuha Religious Court accepted the Defendants' exception on the basis of the consideration that the Plaintiffs' lawsuit lacked parties (plurium litis consortium), the Panel of Judges considered that the lawsuit filed by the Plaintiffs did not involve all parties who should be involved in the case, so it did not meet the formal requirements required in the judicial process, based on this fact the panel of judges then ruled that the lawsuit could not be accepted or Niet Ontvankelijke Verklaard (N.O). The formulation of the problem in the study is